Chronic starvation induces microglial cell depletion in an activity-based anorexia model - Valerie Verspohl; Miranda van Egmond; Lilly Kneisel; Friederike Reese; Anna C. Thelen; Nele Korten; Maren Neumann; Lena Schaack; Clara Voelz; Larissa Käver; Beate Herpertz-Dahlmann; Cordian Beyer; et al. (Scientific Reports)
Abstract Anorexia nervosa (AN) is a severe psychiatric disease with a largely unknown pathophysiology. AN leads to reduced brain volume and a disbalance of the gut microbiome suggesting the involvement of the gut-brain-axis. Also, in the activity-based anorexia (ABA) animal model mimicking AN brain volume loss is observed. This study investigated the impact of chronic starvation on brain cell populations and evaluated the potential protective effects of omega-3 fatty acids (FA) and probiotics in rats. We used a chronic ABA model and provided daily oral supplementation of omega-3 FA and probiotics. Immunohistochemistry and qPCR were used to analyze GFAP-positive astrocytes, IBA1-positive microglia, OLIG1/2-positive oligodendrocytes, MAP2-positive neurons and Ki-67-positive proliferating cells in the cerebral cortex and corpus callosum. We found a significant reduction of astrocytes and microglia in all ABA groups, likely due to reduced proliferating cells. Reduced running wheel activity and reduced amount of food needed to sustain body weight were observed in animals with supplementation with omega-3 FA and probiotics but we did not observe alterations in brain cells that could be attributed to these supplementations. Our results indicate that glial cell depletion potentially underlies the diminished brain volume found in ABA rats. Omega-3 FA and probiotics show potential for reducing AN-related symptoms and merit further study as a therapeutic approach.